2020
DOI: 10.3399/bjgp20x710453
|View full text |Cite
|
Sign up to set email alerts
|

Engagement with and delivery of the ‘parkrun practice initiative’ in general practice: a mixed methods study

Abstract: BackgroundThe parkrun practice initiative, a joint collaboration between parkrun and the Royal College of General Practitioners, was launched to encourage general practices to improve the health and wellbeing of patients and staff through participating in local 5 km parkrun events. Why and how practices engage with the initiative is unknown.AimTo investigate engagement with and delivery of the parkrun practice initiative in general practice.Design and settingMixed methods study conducted from April–July 2019 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Early research showed that regular participants in parkrun experienced increases in weekly physical activity levels, improved fitness, and reported health benefits such as better weight control and mental wellbeing ( Stevinson et al, 2015 ). This has led to parkrun being identified as an exemplar intervention in the WHO Global Action Plan on Physical Activity 2018–2030 ( World Health Organization, 2019 ), and by the Royal College of General Practitioners (RCGP) as a form of social prescribing aimed at increasing patient physical activity ( Fleming et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early research showed that regular participants in parkrun experienced increases in weekly physical activity levels, improved fitness, and reported health benefits such as better weight control and mental wellbeing ( Stevinson et al, 2015 ). This has led to parkrun being identified as an exemplar intervention in the WHO Global Action Plan on Physical Activity 2018–2030 ( World Health Organization, 2019 ), and by the Royal College of General Practitioners (RCGP) as a form of social prescribing aimed at increasing patient physical activity ( Fleming et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall bene ts to a community are likely to be much greater than the sum of the bene ts reported by individual participants. Wider bene ts may include improved perceptions of the local area, increased economic activity if participants use local cafes and shops when attending an event (28), community spirit (27,31) and linking stakeholders within a community, as seen in the UK's parkrun practice initiative (32). Previous researchers have used a Social Return of Investment methodology to quantify the wider bene ts due to sport (33).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed explanation of the survey and sampling is published elsewhere. 8 In the current study, practices were those who responded 'undertaken' to the following question: 'which activities suggested in the parkrun practice Toolkit have you adopted? -Include a parkrun page on the practice website, or a link to the parkrun website'.…”
Section: Designmentioning
confidence: 99%
“…An online survey to all 780 parkrun practices (n=780) in the UK, 8 whereby 306 (39.2%) completed it. Of these, 114/306 (37.3%) reported "including a parkrun page on the ir website, or link to the parkrun website", and were included in the current study.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation